A study of damage evolution in high purity nano TBCs during thermal cycling: A fracture mechanics based modelling approach. Issue 8 (July 2017) - Jonnalagadda, Krishna Praveen; Eriksson, Robert; Yuan, Kang; Li, Xin-Hai; Ji, Xiaojuan; Yu, Yueguang; Peng, Ru Lin
Abstract: This work concerns the study of damage evolution in a newly developed high purity nano 8YSZ thermal barrier coating during thermal cyclic fatigue tests (TCF). TCF tests were conducted between 100 °C–1100 °C with a hold time of 1 h at 1100 °C, first till failure and later for interrupted tests. Cross section analysis along the diameter of the interrupted test samples revealed a mixed-type failure and that the most of the damage occurred towards the end of the coating's life. To understand the most likely crack growth mechanism leading to failure, different crack growth paths have been modelled using finite element analysis. Crack growing from an existing defect in the top coat towards the top coat/TGO interface has been identified as the most likely mechanism. Estimated damage by the model could predict the rapid increase in the damage towards the end of the coating's life.